2016
DOI: 10.1584/jpestics.j16-02
|View full text |Cite
|
Sign up to set email alerts
|

Structural diversity of strigolactones and their distribution in the plant kingdom

Abstract: Strigolactones (SLs) are plant secondary metabolites that were first identified as germination stimulants for the root parasitic weeds witchweeds (Striga spp.) and broomrapes (Orobanche and Phelipanche spp.). In the rhizosphere, SLs also promote root colonization by arbuscular mycorrhizal fungi. In plants, SLs as a novel class of plant hormones regulate various aspects of plant growth and development. Herein I discuss structural diversity of naturally occurring SLs and their distribution in the plant kingdom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 56 publications
1
58
0
Order By: Relevance
“…SLs are produced and exuded at extremely low quantities, being active at pico‐ to nanomolar concentrations, and have been reported in a variety of plant species (Andreo‐Jimenez et al, ; Delaux et al, ; Xie, ). A single plant species can produce various types of SLs, and even different varieties of the same plant species appear to synthesize a blend of SL molecules in different quantities (Ruyter‐Spira, Al‐Babili, van der Krol, & Bouwmeester, ; Xie, Yoneyama, & Yoneyama, ).…”
Section: Sl Production In Plants Under Abiotic Stressesmentioning
confidence: 99%
See 1 more Smart Citation
“…SLs are produced and exuded at extremely low quantities, being active at pico‐ to nanomolar concentrations, and have been reported in a variety of plant species (Andreo‐Jimenez et al, ; Delaux et al, ; Xie, ). A single plant species can produce various types of SLs, and even different varieties of the same plant species appear to synthesize a blend of SL molecules in different quantities (Ruyter‐Spira, Al‐Babili, van der Krol, & Bouwmeester, ; Xie, Yoneyama, & Yoneyama, ).…”
Section: Sl Production In Plants Under Abiotic Stressesmentioning
confidence: 99%
“…SLs are mainly produced by the roots, and that their production in the roots is much higher than in the aerial tissues under normal growth conditions (Brewer et al, ; Visentin et al, ; Xie, ; Xie et al, ). In contrast to roots, little and no effects on SL contents were observed in the shoots of L. japonicus and sorghum, respectively, under P‐deficient ( L. japonicus ) or P‐deficient and N‐deficient (sorghum) conditions (Liu et al, ; Yoneyama, Yoneyama, et al, ).…”
Section: Sl Production In Plants Under Abiotic Stressesmentioning
confidence: 99%
“…Since then, the number of isolated SLs has increased steadily. Today, there are more than 25 known natural SLs (Ćavar, Zwanenburg, & Tarkowski, ; Xie, ) characterized by a common structure consisting of butenolide ring (D‐ring) coupled in R ‐configuration via an ethol ether bridge to a tricyclic lacton (ABC‐ring) in canonical SLs, such as strigol, or to a less conserved moiety in non‐canonical ones (Al‐Babili & Bouwmeester, ; Jia, Baz, & Al‐Babili, ). Stereoconfiguration of the B/C junction, modifications of the ABC ring and structural variations of non‐canonical SLs give rise to the diversity of natural SLs (Al‐Babili & Bouwmeester, ; Jia et al, ; Zwanenburg & Pospíšil, ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the chemical structure of 1 was determined to be methyl (2E,3E)-4-((R,S)-3,3-dimethyl-2-(3-methylbut-2-en-2-yl)-5-oxotetrahydrofuran-2-yl)-2-((((R)-4-methyl-5-oxo-2,5-dihydrofran-2-yl) oxy) methylene) but-3-enoate, which was named methyl zealactonoate. 6) Although 1 contains only the D-ring moiety of canonical SLs and thus is classified as a non-canonical SL, 2) feeding experiments with 13 C-CL confirmed that 1 is synthesized from CL in maize plants (Supplemental Fig. S7).…”
mentioning
confidence: 87%
“…5) SL1 and SL2 were found to have the molecular weights of 348 and 276, respectively. Herein we report the isolation and structure determination of SL2, named methyl zealactonoate, 6) and its germination stimulation activities on S. hermonthica, Phelipanche ramosa, and Orobanche minor seeds.…”
mentioning
confidence: 99%